Предмет: Алгебра,
автор: ученик4117
корень из х-1 = х-3
Помогите пожалуйста решить. Нужно подробное решение, а то никак не разберусь как это решать
Ответы
Автор ответа:
0
√(х-1)=х-3 х-1≥0 ⇒ х≥1
х-1=х²-6х+9
х²-7х+10=0
х₁,₂=7⁺₋√(49-40)=7⁺₋3
2 2
х₁=5 х₂=2
х-1=х²-6х+9
х²-7х+10=0
х₁,₂=7⁺₋√(49-40)=7⁺₋3
2 2
х₁=5 х₂=2
Похожие вопросы
Предмет: История,
автор: Аноним
Предмет: Геометрия,
автор: isakovaalena1405
Предмет: Химия,
автор: kekovq4
Предмет: Обществознание,
автор: guliyagrimes
Предмет: География,
автор: Stradivary